Use of Technology in English Language Learning: Challenges and Benefits - Sari, Nadia Mayang; Abrar, Mukhlash (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The integration of technology in English language learning has gained significant attention due to its potential to enhance learning experiences and outcomes. However, its implementation also poses various challenges that need to be addressed. This study aims to explore the major challenges faced by teachers and students in integrating technology into English language learning classrooms, as well as the potential benefits it offers. A mixed-methods approach was employed, combining quantitative data from pre- and post-tests and qualitative data from classroom observations, interviews, and questionnaires. The findings reveal significant challenges, including limited access to technology, lack of digital literacy, and pedagogical considerations. Conversely, the benefits encompass increased motivation, exposure to authentic language resources, personalized learning, and multimodal experiences. By understanding these challenges and leveraging the advantages, educators and stakeholders can make informed decisions and implement effective strategies to optimize technology integration in language classrooms, ultimately enhancing learning experiences and outcomes.